2016
DOI: 10.1038/tp.2016.184
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up proteomics suggests an association between differential expression of mitochondrial proteins and chronic fatigue syndrome

Abstract: Chronic fatigue syndrome (CFS) is a debilitating and complex disorder characterized by unexplained fatigue not improved by rest. An area of investigation is the likely connection of CFS with defective mitochondrial function. In a previous work, we investigated the proteomic salivary profile in a couple of monozygotic twins discordant for CFS. Following this work, we analyzed mitochondrial proteins in the same couple of twins. Nano-liquid chromatography electrospray ionization mass spectrometry (nano-LC-MS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 46 publications
7
37
1
Order By: Relevance
“…Elevated TORC1 activity was recently observed in ME/CFS cells (lymphoblasts) and this was accompanied by inefficient mitochondrial ATP synthesis and abnormally high, presumably compensatory expression of mitochondrial proteins [41]. Elevated expression of mitochondrial proteins has also been found in other studies of patient saliva, lymphocytes and platelets [41,[49][50][51]. Furthermore, reduced creatine kinase (CK) levels in the serum of people with ME/CFS may suggest reduced cellular CK presence [15], which could contribute to inefficient ATP synthesis given the enzyme's roles in ATP homeostasis [52].…”
Section: Inefficient Atp Synthesis and Abnormal Energy Stress Signallingmentioning
confidence: 76%
“…Elevated TORC1 activity was recently observed in ME/CFS cells (lymphoblasts) and this was accompanied by inefficient mitochondrial ATP synthesis and abnormally high, presumably compensatory expression of mitochondrial proteins [41]. Elevated expression of mitochondrial proteins has also been found in other studies of patient saliva, lymphocytes and platelets [41,[49][50][51]. Furthermore, reduced creatine kinase (CK) levels in the serum of people with ME/CFS may suggest reduced cellular CK presence [15], which could contribute to inefficient ATP synthesis given the enzyme's roles in ATP homeostasis [52].…”
Section: Inefficient Atp Synthesis and Abnormal Energy Stress Signallingmentioning
confidence: 76%
“…There is also evidence that NAD + levels may be elevated in CFS patients (Ciregia et al 2016; Mikirova et al 2012; Naviaux et al 2016). Furthermore, the dysfunction of the TCA cycle in CFS patients reported by (Yamano et al 2016), inhibition of glycolysis and reduced levels of pyruvate reported by (Armstrong et al 2015) and inactivated AMPK together with subnormal levels of IL-6 in the striated muscles of CFS patients reported by (Brown et al 2015) are all abnormalities consistent with a pattern of metabolic downregulation associated with the cellular hibernation associated with endotoxin tolerance.…”
Section: Can Immune and Metabolic Abnormalities Be Explained By Endotmentioning
confidence: 99%
“…These data reinforce the low probability of finding any meaningful abnormality in the blood. A series of interesting but preliminary studies have used proteomics, metabolomics and microbiome analyses in cross‐sectional case–control studies of patients with CFS. As these approaches measure hundreds to thousands of variables, the studies have uniformly included tens of subjects only, and the technologies are relatively new and evolving, any preliminary findings require independent replication in larger cohorts.…”
Section: Pathophysiologymentioning
confidence: 99%